Contra la exclusión Propuesta del ingreso ciudadano - LO VUOLO, Rubén; BARBEITO, Albeto; GARGARELLA, Roberto; OFFE, Claus; OVEJERO LUCAS, Félix; PAUTASSI, Laura; PARIJS, Philippe van (MIÑO Y DAVILA, 2004)
ESTADO BENEFACTOR